Trauma‐informed mental health practice during COVID‐19: Reflections from a Community of Practice initiative. (16th May 2022) - Macedo, Davi Manzini; Reilly, Julie‐Anne; Pettit, Sophie; Negoita, Carmen; Ruth, Laura; Cox, Elizabeth; Staugas, Rima; Procter, Nicholas
ABSTRACT: This article discusses insights arising from a Community of Practice (CoP) initiative within a mental health short stay inpatient unit adjacent to a major Emergency Department to explore how COVID‐19 has influenced engagement and support of people in mental distress. The present initiative was designed as a collaboration between the University of South Australia and SA Health. Community of Practice (CoP) is combined with a narrative review of current evidence to explain specific nursing care responses within an operating environment of pandemic‐induced fear and uncertainty. Meetings discussed the challenges associated with delivering mental health care for people experiencing mental health distress in the COVID‐19 context. Applying trauma‐informed principles to mental health care delivery was identified to be of relevance in the context of an ongoing pandemic. Humanizing nursing care and increasing people's sense of predictability and safety contributed to therapeutic engagement and support during COVID‐19. Factors discussed to mitigate the effects of safety measures include, for example, nuanced verbal and non‐verbal engagement of health workers with people in mental distress when wearing personal protective equipment (PPE). We highlight the need to 'humanise' nursing and openly communicating that both practitioners and people in distress are navigating special circumstances. The CoP participants additionally acknowledged that the experience of moral distress among frontline health workers needs to be addressed in future policy responses to COVID‐19. Person‐centred and trauma‐informed responses at the point of care might help to mitigate the pandemic short‐ and long‐term effects for both service users and frontline health workers.